2021
DOI: 10.37107/jhas.137
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction among the Patients Attending Himalaya Eye Hospital, Pokhara, Nepal

Abstract: Introduction: Patient satisfaction is one of the key elements for the overall improvement of health service management. Patient satisfaction in the health care organization is popularly used for benchmark and accreditation purposes. Methods: A quantitative cross-sectional study was conducted among the 164 patients who got their at least one type of eye surgery done following at least three OPD visits at Himalaya Eye Hospital from January 2019 to July 2019. A systematic random sampling technique was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Overall patient' satisfaction towards eye care provided by the Lúrio University Clinic was assessed using a 20-item patient satisfaction questionnaire. We found that 52.6% of patients were satisfied with eye health services received, a similar result was demonstrated in the study conducted in the National Institute of Ophthalmology in Vietnam (50%) and in Himalaya Eye Hospital in Nepal (51.2%) [21] [22].…”
Section: Discussionsupporting
confidence: 82%
“…Overall patient' satisfaction towards eye care provided by the Lúrio University Clinic was assessed using a 20-item patient satisfaction questionnaire. We found that 52.6% of patients were satisfied with eye health services received, a similar result was demonstrated in the study conducted in the National Institute of Ophthalmology in Vietnam (50%) and in Himalaya Eye Hospital in Nepal (51.2%) [21] [22].…”
Section: Discussionsupporting
confidence: 82%